The Role of Village Apparatus Communication in an Effort to Improve the Quality of Community Services - Desta Periaman Laowo; Yoel Melsaro Larosa; Syah Abadi Mendrofa; Sukaaro Waruwu (Manunggal Halim Jaya, 2024)
The Role of Village Officials' Communication in Efforts to Improve the Quality of Public Services in Sifalaete Village, Gunungsitoli Idanoi District, Gunungsitoli City. This study aims to analyze the role of communication among officials in Sifalaete Village, Gunungsitoli Idanoi District, Gunungsitoli City, and to determine the quality of public services in Sifalaete Village, Gunungsitoli Idanoi District, Gunungsitoli City. To achieve these objectives, the researcher processed the data using qualitative descriptive methods, utilizing in-depth interviews as the instrument and employing purposive sampling techniques, which involved questioning one key informant and six supporting informants. Based on the analysis, the following conclusions can be drawn: The research findings indicate that village officials' communication plays a crucial role in enhancing the quality of public services. The findings highlight the importance of effective interpersonal communication, transparency, and community participation in decision-making processes. These research findings have significant implications for the development of strategies and policies to enhance the quality of public services at the village level. Recommendations are provided to improve training and development of communication skills for village officials, strengthen communication-oriented leadership, and enhance organizational support to facilitate effective communication between village government and the community.